Relationship between concentration of heavy metals in bladder cancer tissue and molecular types using luminal GATA3 and basal cytokeratin 5/6 markers - Bedeir Ali-El-Dein; Mahmoud Abdelgawad; Mona Abdel-Rahim; Islam M. Gomaa; Islam I. Elnaggar; Faten Zahran; Afrah F. Salama; Akaber T. Keshta; Amro E. Mohamed; Hazem H. Saleh; Wael I. Mortada; Afaf M. Attia; et al. (Journal of Trace Elements in Medicine and Biology, 2026)

In vitro regeneration of microplants via protoplast fusion of two Cucumber cultivars (cucumis sativus L.) - Shakil Rahman Shoagh; Abdur Rahim; A. T. K. Mim; Baishakhi Roy; Jakia Sultana; M. Nasiruddin (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

P22-03 Innovative Decision Tree Framework Enhances Safety Assessment of Nanomaterials in Consumer Healthcare Products - T. Rahim; N. Jones; A. Bradley; J.L. Rowland; H. Flockton; A. Rawling (Toxicology Letters, 2025)

Harnessing deep learning for fusion-based heavy metal contamination index prediction in groundwater - Ali Asghar Rostami; Zahra Sedghi; Ata Allah Nadiri; Rahim Barzegar; Natasha T. Dimova; Venkatramanan Senapathi; Abu Reza Md. Towfiqul Islam (Journal of Contaminant Hydrology, 2025)

Molecular and morphological examinations show diversity in the genus Amphidromus (Camaenidae: Stylommatophora) in Bangladesh - Takumi Saito; Takahiro Hirano; T. S. Rupamoy Tanchangya; Rahim Badsha; Yasuto Ishii; Shovon Mohammad Shariar (Systematics and Biodiversity, 2024)

Multi-step ahead soil temperature forecasting at different depths based on meteorological data: Integrating resampling algorithms and machine learning models - Khabat KHOSRAVI; Ali GOLKARIAN; Rahim BARZEGAR; Mohammad T. AALAMI; Salim HEDDAM; Ebrahim OMIDVAR; Saskia D. KEESSTRA; Manuel LÓPEZ-VICENTE (Pedosphere, 2023)

Carbon dots synthesized from microorganisms and food by-products: active and smart food packaging applications - Mehran Moradi; Rahim Molaei; Seyedeh Alaleh Kousheh; Jonas T. Guimarães; David Julian McClements (Critical Reviews in Food Science and Nutrition, 2023)

Targeting de novo loss-of-function variants in constrained disease genes improves diagnostic rates in the 100,000 Genomes Project - Eleanor G. Seaby; N. Simon Thomas; Amy Webb; Helen Brittain; Ana Lisa Taylor Tavares; J. C. Ambrose; P Arumugam; R Bevers; M Bleda; F Boardman-Pretty; C. R. Boustred; H Brittain; et al. (Human Genetics, 2023)
Background Genome sequencing was first offered clinically in the UK through the 100,000 Genomes Project (100KGP). Analysis was restricted to predefined gene panels associated with the patient’s phenotype. However, panels rely on clearly characterised phenotypes and risk missing diagnoses outside of the panel(s) applied. We propose a complementary method to rapidly identify pathogenic variants, including those missed by 100KGP methods. Methods The Loss-of-function Observed/Expected Upper-bound Fraction (LOEUF) score quantifies gene constraint, with low scores correlated with haploinsufficiency. We applied DeNovoLOEUF, a filtering strategy to sequencing data from 13,949 rare disease trios in the 100KGP, by filtering for rare, de novo, loss-of-function variants in disease genes with a LOEUF score < 0.2. We compared our findings with the corresponding patient’s diagnostic reports. Results 324/332 (98%) of the variants identified using DeNovoLOEUF were diagnostic or partially diagnostic (whereby the variant was responsible for some of the phenotype). We identified 39 diagnoses that were “missed” by 100KGP standard analyses, which are now being returned to patients. Conclusion We have demonstrated a highly specific and rapid method with a 98% positive predictive value that has good concordance with standard analysis, low false-positive rate, and can identify additional diagnoses. Globally, as more patients are being offered genome sequencing, we anticipate that DeNovoLOEUF will rapidly identify new diagnoses and facilitate iterative analyses when new disease genes are discovered.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Social acceptance of solar energy in Malaysia: users’ perspective - K. H. Solangi; R. Saidur; M. R. Luhur; M. M. Aman; A. Badarudin; S. N. Kazi; T. N. W. Lwin; N. A. Rahim; M. R. Islam (Clean Technologies and Environmental Policy, 2015)

Gene Polymorphisms of IL-10 and MxA in Responders and Non-responders to Interferon Therapy in HCV Egyptian Patients Genotype 4 - Olfat G. Shaker; Mohamed T. Abdel-Rahim; Salma T. Bayoumi (Cell Biochemistry and Biophysics, 2015)

Effects of Opioid Tolerance and Withdrawal on the Immune System - Toby K. Eisenstein; Rahil T. Rahim; Pu Feng; Nita K. Thingalaya; Joseph J. Meissler (Journal of Neuroimmune Pharmacology, 2006)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)